The Effect of Sleep Duration on Systolic Pressure And Nitric Oxide Concentration in Hypertensive Patients - Riskiyah Riskiyah; Ermin Rachmawati; Mukhamad Nur Kholis (Faculty of Medicine and Health Science, Universitas Islam Negeri Maulana Malik Ibrahim, 2022)
Background: Poor blood pressure control of hypertensive patients is caused partially by bad lifestyle management, which increases the risk of a cardiovascular event by stimulating the defective endothelial function. Objective: This study aimed to investigate the effect of night sleep duration on systolic blood pressure and Nitric Oxide concentration in hypertensive patients. Methods: 60 hypertensive patients age 40 years based on the medical record participated in this study. The sleep duration and sleep quality were performed using the PSQI questionnaire. The 40 participants thus selected randomly for the NO concentration assay using NO Salivary Elisa Kit ab65238. Results: 53 participants experienced night sleep duration ≤ 6 hours, and 44 (73.7%) participants had poor sleep quality. Night sleep duration was associated significantly with hypertensive patients' systolic blood pressure (p = 0,000 0.05; Odds ratio=0.008). Conclusion: The longer duration of sleep at night among hypertension patients, the lower systolic pressure were found. There was no correlation between night sleep duration on NO concentration (p 0.05). These findings provide evidence that night sleep duration is associated strongly with the increased systolic blood pressure but not directly caused by the alteration of endothelial function.Keywords: sleep duration. systolic blood pressure, hypertension, endothelial function, Nitric Oxide